DESIGNING VOCABULARY EXERCISE BOOK WITH WEBTOON COMIC FOR A-1 CLASS YEAR-2 STUDENTS - Sahrini, Elda; Wardah, Wardah (Journal of English Education Program, 2021)
AbstractThe objective of this research is to design a comic book for extensive reading material and this research is classified as Research and Development (R & D). The final product of this research is a comic book for enrichment for students of A-1 class year-2 English Study Program of Tanjungpura University. The comic book is also following the steps of making vocabulary exercise comic book inspired by online comic. The data collection of this research is obtained through questionnaires with 17 students of A-1 class as the research subjects. Based on the table of students’ frequency in reading Webtoon comics, it can be seen that, most of the students are often reading Webtoon comic book (66.7%) while other students (25.9%) are routinely reading Webtoon comic book. There are three pages of exercises in the end of each chapter of this comic book. The exercises are the simple questions related to synonym and antonym of the unfamiliar word found in the story they have been read. It is expected that the students could answer the questions orally or in written form.